Designing for Exploration and Exploitation in Experimental Search and Rescue Scenarios. (September 2021) - Orth, Dylan A.; Buchanan, Michael; Amresh, Ashish; Smith, Cassady; Lematta, Glenn; Cooke, Nancy; Fouse, Adam; Dubrow, Samantha
Exploration and exploitation are commonly cited in search and rescue scenarios to explain the process by which individuals work in a team and gather information about their environment (exploration) and identify potential solutions and adaptations (exploitation) to pursue successful outcomes. In this paper, we discuss exploration and exploitation as critical design features and highlight the importance of balancing them when designing team-based search and rescue missions. To test the proposed design decisions, we developed a usability study that includes two missions wherein teams consisting of three participants are tasked to rescue victims within a Minecraft-based 3D testbed.